Prevalence and key predictors of perinatal depression among postpartum women in Ghana. Issue 2 (20th March 2020) - Sefogah, Promise E.; Samba, Ali; Mumuni, Kareem; Kudzi, William
Abstract: Objective: To determine the prevalence and key predictors of perinatal depression among women in Accra. Method: A two‐step hospital‐based cross‐sectional study from May to July 2016. Patient Health Questionnaire version 9 was administered to postpartum mothers, and those aged 18 years or older with scores above 5 who delivered at LEKMA, Ridge, and Korle Bu Hospitals were recruited. A modified Edinburgh Postnatal Depression Scale was used to assess depression at 2 weeks postpartum. Associations between perinatal depression and sociodemographic/obstetric variables were assessed by χ 2 and multivariate logistic regression. Results: Among 1456 women screened, the prevalence of mental health disorders was 27.5% (400/1456). Of 350 women recruited, perinatal depression at 2 weeks postpartum was 8.6%, 31.6%, and 41.1% at LEKMA, Ridge, and Korle Bu, respectively. Mothers younger than 20 years and older than 35 years at Korle Bu had depression. Vaginal delivery increased the odds of perinatal depression at Ridge and Korle Bu. Blood transfusion was associated with depression at all three hospitals. Conclusion: Blood transfusion, but not other variables, was associated with perinatal depression at 2 weeks postpartum in Accra. Understanding the prevalence of perinatal depression and its associated risk factors in Ghana will aid policy decisions, planning, and clinical management. Abstract : Blood transfusion, but not other clinical or sociodemographic factors, was found to be associated with perinatal depression in Ghana.